DFAL: Diode-Free Adiabatic Logic Circuits. (10th February 2013) - Upadhyay, Shipra; Mishra, R. A.; Nagaria, R. K.; Singh, S. P.
Abstract : The manufacturing advances in semiconductor processing (continually reducing minimum feature size of transistors, increased complexity and ever increasing number of devices on a given IC) change the design challenges for circuit designers in CMOS technology. The important challenges are low power high speed computational devices. In this paper a novel low power adiabatic circuit topology is proposed. By removing the diode from the charging and discharging path, higher output amplitude is achieved and also the power dissipation of the diodes is eliminated. A mathematical expression has been developed to explain the energy dissipation in the proposed circuit. Performance of the proposed logic is analyzed and compared with CMOS and reported adiabatic logic styles. Also the layout of proposed inverter circuit has been drawn. Subsequently proposed topology-based various logic gates, combinational and sequential circuits and multiplier circuit are designed and simulated. The simulations were performed by VIRTUOSO SPECTRE simulator of Cadence in 0.18 μ m UMC technology. In proposed inverter the energy efficiency has been improved to almost 60% up to 100 MHz in comparison to conventional CMOS circuits. The present research provides low power high speed results up to 100 MHz, and proposal has proven to be used in power aware high-performance VLSI circuitry.